Prospective Assessment of Sex‐Related Differences in Symptom Status and Health Perception Among Patients With Atrial Fibrillation. Issue 7 (30th June 2017) - Blum, Steffen; Muff, Christoph; Aeschbacher, Stefanie; Ammann, Peter; Erne, Paul; Moschovitis, Giorgio; Di Valentino, Marcello; Shah, Dipen; Schläpfer, Jürg; Fischer, Andreas; Merkel, Tamara; Kühne, Michael; et al.
Abstract : Background: We prospectively assessed sex‐specific differences in health perception, overall symptom status, and specific symptoms in a large cohort of patients with atrial fibrillation. Methods and Results: We performed a prospective multicenter observational cohort study of 1553 patients with atrial fibrillation. Patients completed questionnaires about personal characteristics, comorbidities, and symptoms on a yearly basis. Mean age was 70±11 years among women and 67±12 years among men. Health perception on a visual analogue scale ranging from 0 to 100 (with higher scores indicating better health perception) was significantly lower in women than in men (70 [interquartile range: 50–80] versus 75 [interquartile range: 60–85]; P <0.0001). More women than men had any symptoms (85.0% versus 68.3%; P <0.0001), palpitations (65.2% versus 44.4%; P <0.0001), dizziness (25.6% versus 13.5%; P <0.0001), dyspnea (35.7% versus 21.8%; P <0.0001), and fatigue (25.3% versus 19.1%; P =0.006). At 1‐year follow‐up, symptoms decreased in both sexes but remained more frequent in women (49.1% versus 32.6%, P <0.0001). In multivariable adjusted longitudinal regression models, female sex remained an independent predictor for lower health perception (ß=−4.8; 95% CI, −6.5 to −3.1; P <0.0001), any symptoms (odds ratio [OR]: 2.6; 95% CI, 2.1–3.4; P <0.0001), palpitations (OR: 2.6; 95% CI, 2.1–3.2; P <0.0001), dizziness (OR: 2.9; 95% CI, 2.1–3.9; P <0.0001), dyspnea (OR: 2.1; 95% CI, 1.6–2.8; P <0.0001), fatigue (OR: 1.6; 95% CI, 1.2–2.2; P =0.0008), and chest pain (OR: 1.8; 95% CI, 1.3–2.6; P =0.001). Conclusions: Women with atrial fibrillation have a substantially higher symptom burden and lower health perception than men. These relationships persisted after multivariable adjustment and during prospective follow‐up.